Battle of Wits: Warfare Cues and Political Orientation Modulate the Perceived Intellect of Allies Versus Adversaries. Issue 3 (April 2018) - Holbrook, Colin; López-Rodríguez, Lucía; Gómez, Ángel
Political conservatism and threat salience have been consistently associated with intergroup bias. However, prior research has not examined potential effects of conservatism and/or threat on the attribution of relative in-group/out-group intelligence. In a cross-cultural study conducted in Spain and the United Kingdom, priming violent conflict with ISIS led participants to view an in-group ally as relatively more intelligent than an out-group adversary, in an effect mediated by feelings of anger (but not fear or general arousal). Conservatism similarly predicted biased perception of the ally's relative intellect, a tendency that was driven by militaristic (not social/fiscal) political attitudes but was not explained by associated increases in state anger following conflict cues. This overall pattern indicates that conflict cues and militaristic political orientation heighten assessments of relative intergroup intellect during warfare via distinct affective and attitudinal pathways.